KEDUDUKAN DISKRESI PEJABAT PEMERINTAHAN - Taufiqurrahman, Muhammad (Pascasarjana UDA, 2019)
This research aims at finding (1) the definition of government officer’s discretion and (2) how is the position of government officer’s discretion. The research method used with the type of research used is empirical legal research. Empirical legal research is a legal research method that functions to be able to see the law in the real sense and examine how the law works in a community environment, the specification of this research is descriptive, with the intention to describe the existing conditions by using scientific research methods and solving problems based on data and facts collected as they were at the time the research was conducted. The conclusions in the discussion of Understanding Government Officials Discretion is the policy of government officials in deciding what actions / actions are without the provisions of the rules, laws or applicable laws but on the basis of wisdom, consideration or justice. Discretionary Position for Government Officials is a decision / action applied to Government Officials in overcoming the concrete problems faced by the administration of government in legislation that gives choices, does not regulate, isincomplete or unclear and or there is government stagnation. Recommendations Expected Discretion Government Officials have legal certainty, so as to create a sense of security and comfort in taking policies without being given the fear of punishment. Discretionary position for Government Officials does not need to hesitate in making decisions / actions to keep referring to the interests and welfare of the community.